2020
DOI: 10.14258/jcprm.2020014678
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Amino Acid Content of Glycyrrhiza Glabra Overground and Underground Parts

Abstract: The purpose of the research was a comparative study of the amino acid composition and the quantitative content of individual amino acids in the over-ground and underground parts of Glycyrrhiza glabra L. (Fabaceae) growing in the Volgograd region. Previously, using the reaction with ninhydrin, as well as carrying out TLC on the plates «Silufol», the presence of amino acids in watery extracts from the samples of vegetable raw materials was established. On an AAA 400 amino acid analyzer in the underground and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Histidine and cysteine are also considered indispensable in infants. Nedil’ko and Yanitskaya [ 58 ] reported the biological value of licorice grass and a broad spectrum of pharmacological activity associated with its relatively high amino acid content. These findings are consistent with those of Bazekin et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histidine and cysteine are also considered indispensable in infants. Nedil’ko and Yanitskaya [ 58 ] reported the biological value of licorice grass and a broad spectrum of pharmacological activity associated with its relatively high amino acid content. These findings are consistent with those of Bazekin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Histidine and cysteine are also considered indispensable in infants. Nedil'ko and Yanitskaya [58] reported the biological value of licorice grass and a broad spectrum of pharmacological activity associated with its relatively high amino acid content. These findings are consistent with those of Bazekin et al [59] and Fu et al [60], who demonstrated that licorice root extract has a favorable influence on the chemical and amino acid composition of the meat.…”
Section: Amino Acid Composition Of Quail Meatmentioning
confidence: 99%
“…Numerous studies report on the content of amino acids in representatives of such families as Nettle (Urticaceae) [12,13], Oleaster (Elaeagnaceae) [14], Leguminosae (Fabaceae) [15,16], and others [17,18]. It has been proven that amino acids are capable of accumulating both in aboveground plant organs and in underground ones.…”
Section: Introductionmentioning
confidence: 99%